Factors Affecting Online Shopping in Birendranagar, Surkhet - K.C., Harendra (Journal of Nepalese Management and Research, 2023)
Online shopping is a rapidly growing phenomenon these days. There is no doubt that the business environment is rapidly changing today, with the involvement of media and communication technologies changing the way of interaction and persuading consumers to buy their products or change their customer choices. The study’s main goal is to identify the factors influencing online shopping in Birendranagar, Surkhet. Descriptive research and casual comparative are used. The study’s target population is all Birendranagar Surkhet consumers who bought their products online. To collect a sample, the convenience method is used. A structural questionnaire is used to collect responses for the survey. Ease and price factors significantly impact the purchasing behavior of all Birendranagar and Surkhet consumers who used to go far online.